2021
DOI: 10.1101/2021.02.11.21251589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 N501Y introductions and transmissions in Switzerland from beginning of October 2020 to February 2021 – implementation of Swiss-wide diagnostic screening and whole genome sequencing

Abstract: The rapid spread of the SARS-CoV-2 lineages B.1.1.7 (N501Y.V1) throughout the UK, B.1.351 (N501Y.V2) in South Africa, and P.1 (B.1.1.28.1; N501Y.V3) in Brazil has led to the definition of variants of concern (VoCs) and recommendations by the European Center for Disease Prevention and Control (ECDC) and World Health Organization (WHO) for lineage specific surveillance. In Switzerland, during the last weeks of December 2020, we established a nationwide screening protocol across multiple laboratories, focusing fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Laboratory developed tests often offers this flexibility. For example, laboratory developed tests for the detection of L484R, E484K and N501Y (alone or in multiplex) in nasopharyngeal swabs specimen were reported earlier this year, demonstrating excellent clinical performance, and provide an even more economical option in laboratories that have the expertise and infrastructure to validate and perform them 34 , 35 , 36 , 37 . Given surveillance of circulating VOC/VOI remains critical for adequate public health control measures and for investigation of vaccine effectiveness when WGS is unavailable or limited, the Seegene Allplex TM SARS-CoV-2 Variants I assay offers a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory developed tests often offers this flexibility. For example, laboratory developed tests for the detection of L484R, E484K and N501Y (alone or in multiplex) in nasopharyngeal swabs specimen were reported earlier this year, demonstrating excellent clinical performance, and provide an even more economical option in laboratories that have the expertise and infrastructure to validate and perform them 34 , 35 , 36 , 37 . Given surveillance of circulating VOC/VOI remains critical for adequate public health control measures and for investigation of vaccine effectiveness when WGS is unavailable or limited, the Seegene Allplex TM SARS-CoV-2 Variants I assay offers a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining demographic and injury variables did not vary significantly between COV+ and COV-patients. The median ISS in COV+ and COVpatients in our cohort was 9 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The most common mechanism of injury in our population was low-impact falls (64.2%) (Table 1).…”
Section: Patient Populationmentioning
confidence: 93%
“…A fundamental line of defense against COVID-19 infection is the administration of the COVID-19 vaccine, which has been documented to reduce the spread of COVID-19 infection as well as the severity of the infection. 6,7 Previous work by Turer et al found that the vaccination rate in patients admitted due to trauma injury was lower than that of patients admitted with other conditions and was predicted to plateau earlier than in the general population. 8 This relatively lower vaccination rate may leave patients vulnerable to injury at higher risk for COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, SARS‐CoV‐2 mutant variants not only had enhanced transmissibility but also effectively avoided human immune response. For instance, alpha variant with spike protein mutation 69‐70del may escape from host immune system 23 , 24 In addition, the antigenic drift occurred in accumulation of mutations in SARS‐CoV‐2 might be nightmare. Antigen drift is a classical phenomenon in virology.…”
Section: Vaccinationmentioning
confidence: 99%